1996
DOI: 10.1038/nsb0596-452
|View full text |Cite
|
Sign up to set email alerts
|

Insights into protein adaptation to a saturated salt environment from the crystal structure of a halophilic 2Fe-2S ferredoxin

Abstract: Haloarcula marismortui is an archaebacterium that flourishes in the world's saltiest body of water, the Dead Sea. The cytosol of this organism is a supersaturated salt solution in which proteins are soluble and active. The crystal structure of a 2Fe-2S ferredoxin from H. marismortui determined at 1.9 A is similar to those of plant-type 2Fe-2S ferredoxins of known structure, with two important distinctions. The entire surface of the protein is coated with acidic residues except for the vicinity of the iron-sulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
193
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(214 citation statements)
references
References 20 publications
17
193
1
Order By: Relevance
“…A similar structural modification has been reported for the archaeal ferredoxin from Haloarcula marismortui, an extreme halophile [26]. Its N-terminal 30 residues form a loop rich in acidic amino acids and bind a potassium ion in order to adapt to a highly salty environment.…”
Section: Discussionsupporting
confidence: 64%
“…A similar structural modification has been reported for the archaeal ferredoxin from Haloarcula marismortui, an extreme halophile [26]. Its N-terminal 30 residues form a loop rich in acidic amino acids and bind a potassium ion in order to adapt to a highly salty environment.…”
Section: Discussionsupporting
confidence: 64%
“…organic solvents) that are used in industrial processes 57 . The main finding of such studies are that the surfaces of proteins from halophiles contain an excess of acidic residues presumably due to their superior water-binding abilities 56 which would help prevent poor protein solubility in such highly dehydrating conditions [58][59][60] . Other studies have also observed a concomitant reduction in lysine content in proteins from halophiles 61; 62 .…”
Section: Proteins From Halophilic Organisms Show An Increased Amount mentioning
confidence: 99%
“…Circular permutation of the secondary structure units helped identify previously unrecognized homologs, such as the mercury transporter protein MerP (26). This versatility suggests that a fundamental understanding of the fold's dynamical properties may facilitate the design of proteins with tightly regulated, and unique, functional roles (27). The development of "modular" proteins that can be artificially assembled into large functional complexes is also at the heart of modern synthetic biology (28).…”
mentioning
confidence: 99%